TEACHING VOCABULARY IN WRITING A DESCRIPTIVE TEXT BY USING PICTURES - (F12410024), Sovia; Arifin, Zainal; Salam, Urai (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2014)
This research is conducted to investigate how well the use of pictures in teaching descriptive text to improve students vocabulary in writing descriptive text at the seventh grade students of SMP N 3 Singkawang. The method used is a Classroom Action Research in which the resercher taught adjective in writing descriptive text through by using pictures. By using pictures students can improve their vocabulary in writing descriptive text .To collect the data in this classroom action research, the writer and collaborator employed observation checklist table to know students progress in learning descriptive text .The result showed that the student scores were getting better at every cycles where the averge scores of the test increase significantly from72,59 in the first , and 79,55 in the second cycle. That proved that the action hypothesis of this research was accepted. The using of pictures are pretty well in improving students vocabulary in which adjective in writing descriptive text. Keyword: vocabulary, pictures Abstract: Penelitian ini bertujuan untuk mengeahui seberapa baik penggunaan gambar-gambar dalam pengajaran wacana deskripsi untuk memperbaiki kosa kata siswa dalam menulis wacana deskripsi. Metode yang di gunakan adalah Penelitian Tindakan Kelas dimana peneliti mengajarkan kata sifat dalam mengajarkan wacana deskripsi dengan menggunakan gambar sebagai media.dengan menggunakan gambar-gambar siswa-sisa dapat memperbaiki kosa-kata mereka dalam menuls wacana deskripsi. Untuk mengumpulkan data dalam penelitian tindakan kelas ini, penulis dan rekan sejawat menggunakan tabel observasi untuk mengetahui kemajuan siswa dalam mempelajari wacana deskripsi. Hasilnya menunjukkan bahwa nilai siswa semakin baik pada setiap siklus dimana rata-rata nilai meningkat secara signifikan dari 72,59 pada siklus pertama dan 79,55 pada siklus kedua. Itu membuktikan bahwa hipetesis tindakan penelitian ini di terima. Pengguaan gambar cukup baik dalam meningkatkan kosa-katayakni kata sifat dalam menulis wacana deskripsi. Kata kunci: kosa kata, gambar